KEBKEBIJAKAN MODERASI BERAGAMA PADA PEMBELAJARAN PAI DI UNIVERSITAS ISLAM NEGRI SUMATERA UTARA MEDAN - Ainus Syuhud; Khairuddin Bangun; Dian Masrura (Raudhah - Proud To Be Professional, 2024)
This study aims to reveal the Religious Moderation-Based Pie Learning Policy at the State Islamic University of North Sumatra, Medan, by focusing on: 1. Religious Moderation Policy Conducted at the North Sumatran Islamic State University Medan, 2 The implementation of the policy by PAI Lecturers in Religious Moderation-Based Learning in State Islamic University of North Sumatra, Medan, 3. Student Responses to the Policy of Pie Learning Based on Religious Moderation at State Islamic University of North Sumatra, Medan. This article uses a qualitative approach. Data was collected by using interview, observation, and documentation techniques. Data analysis techniques include data reduction, data presentation, and drawing conclusions, checking the validity of the findings by extending participation, source triangulation techniques, theories, methods and persistence of observations. The results of the study illustrate that: 1. UINSU Medan has implemented several policies that support religious moderation, such as the integration of courses with various moderating values, integration of student community service activities based on the values ​​of religious moderation, and collaboration between the Islamic State University of North Sumatra Medan and IAIN loksemawe. to improve the policy of independent learning and religious moderation in the campus environment, 2. Lecturers have internalized religious moderation in learning, 3. Student statements that there are policies carried out by the campus to meet diverse moderation in the campus area, such as the existence of various moderation values ​​that included in the sub-sub-discussions of several courses, counseling on religious moderation in KKN, seminars on religious moderation from campus parties, etc.